2010
DOI: 10.1016/j.virol.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genome characterization of a debilitation-associated mitovirus infecting the phytopathogenic fungus Botrytis cinerea

Abstract: The full-length sequences of Botrytiscinereamitovirus 1 (BcMV1) and an associated RNA (BcMV1-S) in strain CanBc-1c-78 of Botrytis cinerea were determined. Sequence analysis showed that BcMV1 is 2804 nt long and AU-rich (66.8%). BcMV1 shares 95% nucleotide sequence identity with Ophiostomanovo-ulmimitovirus 3b (OnuMV3b). However, it is 472 nt longer than OnuMV3b. Mitochondrial codon usage revealed that BcMV1 contains one open reading frame encoding RdRp, which is 96% identical to the RdRp of OnuMV3b. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 48 publications
2
132
0
Order By: Relevance
“…Nevertheless, the differences in growth among isolates may be also having been due to a genetic influence (Zharare et al, 2010) a possibility not tested here due to not working with genetically similar strains. Previous studies have shown that viruses found in many fungi, e.g., Cryphonectria parasitica, Fusarium graminearum or Botrytis cinerea, produce several phenotypic changes such as reduction in growth and sporulation of the fungal strains they infect (Chu et al, 2002;Boland, 2004;Van Diepeningen et al, 2006;Robin et al, 2010;Wu et al, 2010;Zhang et al, 2010). In our study, the isolates growing at osmotic potential medium of -0.6 MPa and -1.8 MPa also showed a reduction of the mycelial growth.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, the differences in growth among isolates may be also having been due to a genetic influence (Zharare et al, 2010) a possibility not tested here due to not working with genetically similar strains. Previous studies have shown that viruses found in many fungi, e.g., Cryphonectria parasitica, Fusarium graminearum or Botrytis cinerea, produce several phenotypic changes such as reduction in growth and sporulation of the fungal strains they infect (Chu et al, 2002;Boland, 2004;Van Diepeningen et al, 2006;Robin et al, 2010;Wu et al, 2010;Zhang et al, 2010). In our study, the isolates growing at osmotic potential medium of -0.6 MPa and -1.8 MPa also showed a reduction of the mycelial growth.…”
Section: Discussionsupporting
confidence: 62%
“…Mitoviruses have been recorded in several phytopathogenic fungi such as Cryphonectria parasitica (Polashock and Hillman, 1994;Polashock et al, 1997), Ophiostoma novo-ulmi (Brasier, 1983;Rogers et al, 1987), Sclerotina homoeocarpa (Deng et al, 2003;Deng and Boland, 2004), Helicobasidium mompa (Osaki et al, 2005), Chalara elegans (Park et al, 2006) and Botrytis cinerea (Castro et al, 2003;Wu et al, 2007). In most cases, the presence of mitoviruses is associated with reduction of fungal pathogenicity (Ghabrial and Suzuki, 2009;Wu et al, 2010). Members of the genus Mitovirus have also been isolated in G. abietina (Tuomivirta and Hantula, 2003) which, in the Spanish population, has recently been discovered to host (Botella et al, 2012a).…”
Section: Resumen Efecto De Posibles Mitovirus En El Crecimiento In VImentioning
confidence: 99%
“…Depressed production of conidia has been observed for hypovirus-infected strains of C. parasitica (51) and mycovirus-infected strains of Diaporthe ambigua (52). In addition, previous studies indicated that conidium production was reduced significantly in mycovirus-associated, hypovirulent strains of B. cinerea (53,54). Unexpectedly, we found that although wild-type strain KY-1 produced conidia in a normal fashion, SsPV1-infected strains KY-1V1 and KY-1V2 of B. cinerea produced more conidia than did strain KY-1.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, B. cinerea was ranked by fungal pathologists as being the second most important pathogenic fungus based on scientific/economic importance in the journal Molecular Plant Pathology (56). Some hypovirulence-associated mycoviruses from B. cinerea and its related species Botrytis porri have been isolated and characterized (10,54,57), but these Botrytis viruses are unlikely to be used for control of diseases caused by these fungi under field conditions because they are easy to be eliminated via asexual propagation (see below). Expansion of the host range of mycoviruses has been accomplished for many fungus-mycovirus systems (7,8,24,(58)(59)(60)).…”
Section: Discussionmentioning
confidence: 99%
“…To detect the morphology of virions in the hyphal cells, ultrathin fungal sections of the strain AH98 and Ep-EPNA367-PT2 were prepared to detect the morphology of SsNSRV-1 virions under TEM. These ultrathin fungal sections were prepared and observed in accordance with the method described by Wu et al (36).…”
Section: Methodsmentioning
confidence: 99%